Case report: Sphenoid wing dural arteriovenous fistula draining into ophthalmic veins inducing pulsatile tinnitus as the sole symptom and its spontaneous closure - Hsieh, Yue-Lin; Zhong, Jiake; Chen, Xi; Wang, Wuqing (Frontiers in Neurology, 2024)
This case report discusses a unique instance of pulsatile tinnitus (PT) caused by a rare type of intracranial dural arteriovenous fistula (DAVF) located in the sphenoid wing (SW) region, with PT being the sole presenting symptom. The patient initially received multiple misdiagnoses and sought medical attention at various hospitals before being correctly diagnosed. Imaging studies revealed the DAVF's presence in the SW region, which led to the patient's referral to interventional radiology/neurology, although she chose conservative observation without surgical intervention. Remarkably, the patient's PT spontaneously ceased after 30 months without any apparent cause, and follow-up imaging confirmed the absence of DAVF-related abnormalities. The case highlights the importance of considering DAVF as a potential cause of PT, even when there are no evident abnormalities in proximity to the auditory apparatus. It also emphasizes the need for otolaryngologists to extend their examination to include regions beyond the temporal bone, such as the sphenoid bone and orbital areas, when PT is the exclusive symptom. The case underscores the significance of early detection and intervention for DAVFs, as they can lead to debilitating complications, despite the rare occurrence of spontaneous symptom resolution in this case.